Dietary vitamin D2 – a potentially underestimated contributor to vitamin D nutritional status of adults? - Cashman, Kevin D.; Kinsella, Michael; McNulty, Breige A.; Walton, Janette; Gibney, Michael J.; Flynn, Albert; Kiely, Mairead (British journal of nutrition, 2014)
It has been suggested that vitamin D2 is not very prevalent in the human food chain. However, data from a number of recent intervention studies suggest that the majority of subjects had measurable serum 25-hydroxyvitamin D2 (25(OH)D2) concentrations. Serum 25(OH)D2, unlike 25(OH)D3, is not directly influenced by exposure of skin to sun and thus has dietary origins; however, quantifying dietary vitamin D2 is difficult due to the limitations of food composition data. Therefore, the present study aimed to characterise serum 25(OH)D2 concentrations in the participants of the National Adult Nutrition Survey (NANS) in Ireland, and to use these serum concentrations to estimate the intake of vitamin D2 using a mathematical modelling approach. Serum 25(OH)D2 concentration was measured by a liquid chromatography–tandem MS method, and information on diet as well as subject characteristics was obtained from the NANS. Of these participants, 78·7 % (n 884) had serum 25(OH)D2 concentrations above the limit of quantification, and the mean, maximum, 10th, 50th (median) and 90th percentile values of serum 25(OH)D2 concentrations were 3·69, 27·6, 1·71, 2·96 and 6·36 nmol/l, respectively. To approximate the intake of vitamin D2 from these serum 25(OH)D2 concentrations, we used recently published data on the relationship between vitamin D intake and the responses of serum 25(OH)D concentrations. The projected 5th to 95th percentile intakes of vitamin D2 for adults were in the range of 0·9–1·2 and 5–6 μg/d, respectively, and the median intake ranged from 1·7 to 2·3 μg/d. In conclusion, the present data demonstrate that 25(OH)D2 concentrations are present in the sera of adults from this nationally representative sample. Vitamin D2 may have an impact on nutritional adequacy at a population level and thus warrants further investigation.